Tumor-resident memory T cells as a biomarker of the response to cancer immunotherapy - Damei, Isabelle; Trickovic, Tatiana; Mami-Chouaib, Fathia; Corgnac, Stéphanie (Frontiers in Immunology, 2023)
Tumor-infiltrating lymphocytes (TIL) often include a substantial subset of CD8+ tissue-resident memory T (TRM) cells enriched in tumor-specific T cells. These TRM cells play a major role in antitumor immune response. They are identified on the basis of their expression of the CD103 (αE(CD103)β7) and/or CD49a (α1(CD49a)β1) integrins, and the C-type lectin CD69, which are involved in tissue residency. TRM cells express several T-cell inhibitory receptors on their surface but they nevertheless react strongly to malignant cells, exerting a strong cytotoxic function, particularly in the context of blocking interactions of PD-1 with PD-L1 on target cells. These TRM cells form stable conjugates with autologous tumor cells and interact with dendritic cells and other T cells within the tumor microenvironment to orchestrate an optimal in situ T-cell response. There is growing evidence to indicate that TGF- is essential for the formation and maintenance of TRM cells in the tumor, through the induction of CD103 expression on activated CD8+ T cells, and for the regulation of TRM effector functions through bidirectional integrin signaling. CD8+ TRM cells were initially described as a prognostic marker for survival in patients with various types of cancer, including ovarian, lung and breast cancers and melanoma. More recently, these tumor-resident CD8+ T cells have been shown to be a potent predictive biomarker of the response of cancer patients to immunotherapies, including therapeutic cancer vaccines and immune checkpoint blockade. In this review, we will highlight the major characteristics of tumor TRM cell populations and the possibilities for their exploitation in the design of more effective immunotherapy strategies for cancer.